Nanoindentation measurements of mechanical properties and creep behavior of Niutitang formation shale rocks, China - Wang, Jianfeng; Niu, Jungang; Yang, Chao; Jiang, Wenmin; Li, Yun; Zheng, Yijun; Liao, Yuhong; Feng, Dingyu; Peng, Ping’an; Xiong, Yongqiang (Frontiers in Earth Science, 2025)
Shale is a typical source rock and reservoir rock for oil and gas production. Accurate estimation of its mechanical properties and creep behavior is challenging due to the multiphase and multiscale structure of this rock. In this study, we conducted X-ray diffraction, organic geochemical analysis, and nanoindentation tests on Niutitang shale samples collected from outcrop in the north of Sichuan Province and a shallow well drilled in Guizhou Province, China, to investigate Young’s modulus (E) and contact creep modulus (C) at different scales. To upscale these parameters, we used the Voigt-Reuss-Hill (VRH) model; and analyzed the controlling factors on the variations of mechanical and creep properties for these shales. The results showed that the E of organic matter of the Niutitang Formation shales varied slightly, while the hardness (H) and C varied widely. Grid nanoindentation and k-means clustering revealed three mechanically distinct clusters for these Niutitang Formation shales, with the softest phase being the clay matrix phase, with E, H, and C values of 26.6–52.0, 1.7–3.1, and 869–1945 GPa, respectively. Based on the VRH model, the E and C values of the Niutitang shale are 25.8–43.6 and 1131–2643 GPa, respectively. The constituent content has a relatively stronger controlling effect on the contact creep modulus than the Young’s modulus for the Niutitang Formation shale. This study will help us optimize hydraulic fracture design and evaluate well stability, as well as assess the fracturability and recovery potential of Niutitang shale reservoirs, thereby guiding the efficient development of its shale gas.